Analysis Of Financial Statements In Measuring Profitability At Pt Sariguna Primatirta Tbk (Cleo) - Anjani, Lale Mihram; Septika, Baiq Herdina; Wijaya, I Ketut Kusuma (Mandalika Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the level of profitability of PT Sariguna Primatirta Tbk (CLEO) as an indicator of the company’s financial performance during the period 2022–2024. The research method used is descriptive quantitative with a case study approach. The data employed in this study are secondary data obtained from the company’s annual financial statements published through the Indonesia Stock Exchange (IDX). The data analysis technique uses profitability ratio analysis, including Net Profit Margin (NPM), Gross Profit Margin (GPM), Return on Assets (ROA), and Return on Equity (ROE), as well as trend analysis using the Least Square method. The results of the study indicate that the profitability of PT Sariguna Primatirta Tbk shows a consistent increase throughout the research period. The Net Profit Margin (NPM) increased from 11.5% in 2022 to 14.6% in 2023 and further rose to 17.6% in 2024. Gross Profit Margin (GPM) also demonstrated a positive trend, increasing from 50.5% in 2022 to 56.6% in 2023 and 58.3% in 2024. Return on Assets (ROA) increased from 10.8% in 2022 to 13.3% in 2023 and reached 17.8% in 2024. Meanwhile, Return on Equity (ROE) rose from 15.9% in 2022 to 20.2% in 2023 and 24.6% in 2024. The trend analysis results show that all profitability ratios tend to increase, indicating an improvement in the company’s financial performance. Therefore, it can be concluded that PT Sariguna Primatirta Tbk has a good level of profitability and continues to experience growth, reflecting the company’s ability to effectively manage its assets.